(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The chemical composition of the plant is complex and varied. In addition to carbohydrates, proteins and oils, it was found to contain biologically active substances,such as a, E and K, from vitamins that are beneficial and important for the human body. It was found that these biologically active substances are used in the treatment of several diseases caused by; conjunctivitis, anemia, ischemic heart attack.